Native t1 mapping magnetic resonance imaging as a quantitative biomarker for characterization of the extracellular matrix in a rabbit hepatic cancer model - Keller, Sarah; Borde, Tabea; Brangsch, Julia; Adams, Lisa C.; Kader, Avan; Reimann, Carolin; Gebert, Pimrapat; Hamm, Bernd; Makowski, Marcus (Biomedicines, 2020)
To characterize the tumor extracellular matrix (ECM) using native T1 mapping magnetic resonance imaging (MRI) in an experimental hepatic cancer model, a total of 27 female New Zealand white rabbits with hepatic VX2 tumors were examined by MRI at different time points following tumor implantation (day 14, 21, 28). A steady-state precession readout single-shot MOLLI sequence was acquired in a 3 T MRI scanner in prone position using a head-neck coil. The tumors were segmented into a central, marginal, and peritumoral region in anatomical images and color-coded T1 maps. In histopathological sections, stained with H&E and Picrosirius red, the regions corresponded to central tumor necrosis and accumulation of viable cells with fibrosis in the tumor periphery. Another region of interest (ROI) was placed in healthy liver tissue. T1 times were correlated with quantitative data of collagen area staining. A two-way repeated-measures ANOVA was used to compare cohorts and tumor regions. Hepatic tumors were successfully induced in all rabbits. T1 mapping demonstrated significant differences between the different tumor regions (F(1.43,34.26) = 106.93, p < 0.001) without interaction effects between time points and regions (F(2.86,34.26) = 0.74, p = 0.53). In vivo T1 times significantly correlated with ex vivo collagen stains (area %), (center: r = 0.78, p < 0.001; margin: r = 0.84, p < 0.001; peritumoral: r = 0.73, p < 0.001). Post hoc tests using Sidak’s correction revealed significant differences in T1 times between all three regions (p < 0.001). Native T1 mapping is feasible and allows the differentiation of tumor regions based on ECM composition in a longitudinal tumor study in an experimental small animal model, making it a potential quantitative biomarker of ECM remodeling and a promising technique for future treatment studies.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Extracellular matrix; Liver cancer; Magnetic resonance imaging; Rabbits; T1 mapping; VX2